2002
DOI: 10.1023/a:1014963313559
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: In the present study, we investigated the effect of Ginkgo biloba extract, EGb 761, and one of its components, bilobalide, on gene expression of subunit 1 of mitochondrial NADH dehydrogenase (ND1) in PC12 cells. By Northern blot analysis we found a approximately 2-fold significant increase in NDI mRNA level, after 48 and 72 h exposure to 100 microg/ml EGb 761 and to 10 microg/ml bilobalide. We also evaluated, by oxygraphy measurements, mitochondrial respiration during state 3 and state 4. In cells treated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(9 citation statements)
references
References 30 publications
1
7
0
1
Order By: Relevance
“…Although further studies are necessary, we can speculate that a GBE treatment may not only enhance mtDNA as an early event after acute treatment, but may instigate mitochondria biogenesis as a long-term effect after chronic exposure [42]. In line with this idea, recent studies showed that GBE induced hippocampal neurogenesis, a very energy demanding process, in young and old transgenic AD mouse model (TgAPP/PS1) after receiving a diet supplemented with GBE for 1 month [43].…”
Section: Discussionmentioning
confidence: 77%
“…Although further studies are necessary, we can speculate that a GBE treatment may not only enhance mtDNA as an early event after acute treatment, but may instigate mitochondria biogenesis as a long-term effect after chronic exposure [42]. In line with this idea, recent studies showed that GBE induced hippocampal neurogenesis, a very energy demanding process, in young and old transgenic AD mouse model (TgAPP/PS1) after receiving a diet supplemented with GBE for 1 month [43].…”
Section: Discussionmentioning
confidence: 77%
“…These events may increase stress resistance and stabilize the cellular redox state in living organisms [40, 88, 89]. Bilobalide upregulates two mitochondrial DNA-encoded genes: subunit III of cytochrome c oxidase (complex IV) and subunit ND1 of NADH dehydrogenase (complex I) of the respiratory chain, indicating a fundamental mechanism that may underline EGb 761 induced neuroprotection [90, 91]. Enhancement of the respiratory control ratio, improving ATP synthesis, and preserving the mitochondrial outer membrane integrity prevent cyt c release, thereby blocking the formation of the apoptosome and the apoptotic caspase cascade [89].…”
Section: Antiapoptotic Mechanisms From Egb 761mentioning
confidence: 99%
“…Enhancement of the respiratory control ratio, improving ATP synthesis, and preserving the mitochondrial outer membrane integrity prevent cyt c release, thereby blocking the formation of the apoptosome and the apoptotic caspase cascade [89]. Tendi et al [91] suggest that EGb 761 and bilobalide might indirectly increase ND1 transcription by modulating the expression and/or the binding of transcription factors in the promoters of genes involved in mitochondrial transcription. In addition, both flavonoid and terpenoid constituents of EGb 761 decrease the expression of iNOS, which might oppose the deleterious effects of excessive production of NO • [92], which inhibit the complex I of respiratory chain by S-nitrosation, tyrosine nitration, and damage to FeS centers [93] and could increase Bax expression and decrease Bcl-2 expression subsequently leading to neural death [94].…”
Section: Antiapoptotic Mechanisms From Egb 761mentioning
confidence: 99%
“…This extract increases the rate of acetylcholine turnover and stimulates binding activity of ligands to muscarinic receptors in the hippocampus [ 88 ]. G. biloba cures cognitive deficits and dementia [ 31 , 89 ] and also has antioxidant and free radical scavenging activity in animals [ 90 , 91 , 92 ]. The multiple effects G. biloba can be attributed to the different components of the extract, which may act independently or synergistically.…”
Section: Bioactive Compounds That Improve Learning and Memorymentioning
confidence: 99%